Evaluation of herbicide mixtures for broad-spectrum weed suppression and yield improvement in onion (Allium cepa L.) under post rainy season conditions - Panda, Urmila; Dash, Rabiratna; Mohapatra, Bijay Kumar; Tripathy, Pradyumna; Nayak, Rabindra Kumar; Mohapatra, Araya Kumar Biswamohan (Plant Science Today, 2026)
Onion (Allium cepa L.) is highly susceptible to weed infestation because of its slow initial growth, short stature, shallow roots and lack of dense foliage. The weed problem severely influences crop growth and bulb yield. In most production systems, weed control relies on manual weeding, which is labour-intensive and costly. Therefore, the current investigation was carried out at the Agronomy Main Research Farm of Odisha University of Agriculture and Technology, Bhubaneswar, Odisha, India to evaluate different herbicides application and their effect on weed and crop growth. The experiment was laid out under post rainy season during December to March consecutively for 2 years in randomized block design with 8 treatments and 3 replications. Application of Oxyfluorfen 23.5 % emulsifiable concentrate (EC) at 100 g a.i. ha-1 followed by a post-emergence ready mix (RM) application of quizalofop-ethyl 4 % + oxyfluorfen 6 % EC at 100 g a.i. ha-1 resulted in higher weed control efficiency (WCE) (83.83 %) and herbicidal efficiency index (HEI) (18.84 %). The yield advantage was approximately 275 % over weedy check and 31 % over 3 manual weeding (p ≤ 0.05). The desirable yield traits like bulb equatorial diameter, polar diameter, neck thickness, percentage of bolters, doubles and different grades of (A, B and C) bulbs were significantly influenced with the above combination of herbicide over all tested herbicides and manual weeding. The residue analysis of harvested soil and crop through high-performance liquid chromatography (HPLC) analysis showed residues below the maximum residue limit (MRL). The result confirms that Oxyfluorfen 23.5 % EC at 100 g a.i. ha-1 fb Quizalofop-ethyl 4 % + Oxyfluorfen 6 % EC (RM) at 100 g a.i. ha-1 is a suitable herbicide combination for managing broad spectrum weeds in onion.